The Role of Entrepreneurship Learning in Developing the Entrepreneurial Spirit of High School and Vocational High School Students: A Systematic Literature Review - Aida Dwipriwanti; Sarah Sakiran Salsabila; Sudarmiatin Sudarmiatin; Mokhammad Nuruddin Zanky (International Forum of Researchers and Lecturers, 2025)
This study aims to systematically review various studies that discuss the role of entrepreneurship education in developing students’ entrepreneurial spirit at the Senior High School (SMA) and Vocational High School (SMK) levels. The method used is the Systematic Literature Review (SLR), guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The reviewed articles cover publications from 2019 to 2025. Based on the selection of 20 scientific articles, the findings indicate that entrepreneurship education plays an important role in enhancing students’ creativity, innovation, self-confidence, and independence. The most effective learning strategies include project-based learning, business simulations, and collaboration with the industrial sector. In addition, teachers play a crucial role as facilitators in fostering an entrepreneurial mindset. The challenges identified include limited resources, insufficient teacher training, and suboptimal school policy support. Overall, entrepreneurship education has been proven to make a significant contribution to shaping entrepreneurial character and preparing students to face the challenges of the workforce.